Prosthetic Rehabilitation of Patient with Total Maxillectomy with Hollow Bulb Closed Obturator and Cast Partial Denture: A Clinical Report - Neupane, G.; Sapkota, B. (Journal of Nepalese Prosthodontic Society, 2021)
Total maxillectomy is the complete resection of one of the two maxillae or resection to the midline. Surgical intervention creates communication between the oral cavity, nasal cavity and maxillary sinus. Postsurgical maxillary defects predispose the patient to hypernasal speech, leakage of food bolus and liquids into the nasal cavity, impaired mastication and various degrees of cosmetic deformities. Prosthodontic rehabilitation with obturator prosthesis restores the missing structures and acts as a barrier between the communications among the various cavities. Hollow bulb obturator with the maximum coverage of the defect aids in retention, stability, support with improved speech resonance and reduced weight on the unsupported side. This clinical report presents the prosthetic management of a patient having total maxillectomy on left side with definitive hollow bulb closed obturator and cast partial denture on the maxilla.